Перспективы развития твердых сплавов в Украине - Бондаренко, В.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The state of the art of the hard alloy production in Ukraine and abroad has been analyzed. The main lines of scientific investigations into the development of new grades of hard alloys and technologies of their production have been substantiated.